DEEP BRANDING STRATEGY ANALYSIS INCREASING MARKET SHARE (Case Study on SMEs in the Fisheries Sector in Kupang City) - Tingga, Chairul Pua (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study is to determine the branding strategy for MSME fishery product processing in increasing market share. The research method used is a qualitative method with a case study approach on SMEs processing fishery products in the form of fish floss, the subjects in this study are SMEs processing fishery products, data collection techniques are observation methods and structured interviews. Data analysis was performed by triangulation (combined). The results of the study show that the branding strategy implemented by MSMEs has not been able to increase the market share of fishery product processing products. Many of them are still not implementing the branding strategy properly.